A Semiotics Study: Visual Signs in Katy Perry’s Selected Music Videos (Universitas Pamulang, 2024)
This study is aimed to show visual sign from “A Semiotics Study: Visual Sign In Katy Perry’s selected music videos.” The discussion is related to the meaning from the visual sign used Denotative and Connotative meaning that can be related to Myth perspective. In this study, the writer used qualitative research method by applying the procedure of descriptive data in the form of written words of the people and their observed behavior. This study used theory from Roland Barthes about semiotics that covered about signifed and signifier which can be seen from denotative and connotative meaning, and myth perspective. The result of the study is the writer found out 30 data that consist of female domination issue by using semiotics analysis. There are 15 data from Dark Horse music video which consist of denotative and connotative meaning and 15 data from Roar music Video. All the signifed and signifer consist of connotative, denotative, and myth meaning that showed about female domination.